2020
DOI: 10.1128/jcm.01687-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ID Fungi Plates Medium for Identification of Molds by MALDI Biotyper

Abstract: MALDI-TOF mass spectrometry (MS) identification of pathogenic filamentous fungi is often impaired by difficulties in harvesting hyphae embedded in the medium and long extraction protocols. The ID Fungi Plate (IDFP) is a novel culture method developed to address such difficulties and improve the identification of filamentous fungi by MALDI-TOF MS. We cultured 64 strains and 11 clinical samples on IDFP, Sabouraud agar-chloramphenicol (SAB), and ChromID Candida agar (CAN2). We then compared the three media for gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For example, Sabouraud dextrose agar (SDA) is a commonly used medium for fungi especially for filamentous fungi [21,22], while blood agar (BA) and chocolate agar (CA) are used for fungi isolated from mycotic keratitis patients [21]. CHROMagarTM Candida medium has been used for Candida separation [23,24], whereas ID fungi plate culture with matrixassisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) is suitable for pathogenic filamentous fungi [25]. Obviously, cultivation of fungi is the most direct method with visualization of fungal morphology and colony color.…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sabouraud dextrose agar (SDA) is a commonly used medium for fungi especially for filamentous fungi [21,22], while blood agar (BA) and chocolate agar (CA) are used for fungi isolated from mycotic keratitis patients [21]. CHROMagarTM Candida medium has been used for Candida separation [23,24], whereas ID fungi plate culture with matrixassisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) is suitable for pathogenic filamentous fungi [25]. Obviously, cultivation of fungi is the most direct method with visualization of fungal morphology and colony color.…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
“…However, there are some limitations in its application. (1) During cultivation, the environmental fungi (e.g., Aspergillus) easily affect the precision of results, and even slight differences in culture process lead to the change in fungi morphology [25]. (2) It is difficult to distinguish specific species and genus of similarly looking fungi even by microscope, and some fungi cannot be cultured in the existing culture modes [26].…”
Section: Culture-dependent Methodsmentioning
confidence: 99%
“…Concerning the difficulties of collecting fungal colonies, we recently evaluated the Id Fungi Plates (IDFP, Quincieux, Lyon, France), a new solid media covered by a porous membrane specifically developed to facilitate the sampling of molds and the identification by mass spectrometry (Table 1). Compared to Sabouraud media, IDFP allowed an easier and therefore faster harvest (92.4% vs. 9.1%), and more identification without the need for off-plate protocols [28]. Other teams also concluded that this media improves the identification of filamentous fungi [29,30].…”
Section: Solutionsmentioning
confidence: 99%
“…However, the identification of filamentous fungi is often compromised by difficulties in the extraction steps and by the fact that some cryptic resistant species are not yet included in the databases. The first problem could be resolved by performing extended extraction procedures [ 22 ] or using special culture media [ 23 ]. Despite the usefulness of MALDI-TOF as a technique, molecular-based identification (DNA sequencing) is still the gold-standard for fungal taxonomy [ 24 ].…”
Section: Intrinsic Resistance Detectionmentioning
confidence: 99%